Gereja dan Kebudayaan - Paulus Eko Kristianto (Dekonstruksi, 2026)
The contextual church is the church that pays attention to the context. One of the contexts facing the church is culture. The church needs to build relationships with the church. This article discusses how church and cultural relations. This relationship includes seeing various theological developments in it. In addition, the author also shows some concrete examples of churches that pay attention to and consider culture as its context.